PEMBUDAYAAN MEMBACA PERMULAAN PADA PESERTA DIDIK KELAS I MELALUI PENERAPAN METODE READ ALOUD - Pina Indah Sayekti; Sutama, Sutama; Achmad Fatoni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe the implementation of the Read Aloud method in fostering early reading habits among first-grade students at MI Muhammadiyah Karanganyar. The approach used in this research is qualitative with a case study design. Data collection methods include interviews, observations, and documentation. Data analysis techniques involve data reduction, data presentation, and drawing conclusions. The findings of this study demonstrate that the implementation of the Read Aloud method at MI Muhammadiyah Karanganyar has proven to have a positive impact on fostering reading habits among first-grade students. Supporting factors include the availability of competent and highly committed teachers, as well as continuous teacher training support. Access to quality and diverse books in the school library also contributes to the success of this oral reading activity. The active role of parents in reinforcing reading habits at home has also been shown to significantly enhance children's interest and reading abilities. However, challenges such as maintaining students' focus and concentration, and the lack of interest among some students who are not accustomed to reading at home, need to be addressed.